An image encryption algorithm based on dynamic row scrambling and Zigzag transformation - Wang, Xingyuan; Chen, Xuan (Chaos, solitons and fractals, 2021)
•Three one-dimensional chaotic maps are improved and two new one-dimensional chaotic systems are proposed.•The dynamic row scrambling in this paper is to traverse odd rows from outside to inside and even rows from inside to outside.•Using different values of the chaotic remainder sequence, the different triangle matrices of the image are zigzag scrambled in different directions and orders. This paper introduces two new one-dimensional chaotic systems. They can be considered as an improvement of Logistic map, Sine map and Tent map. One is the chaotic system composed of Sine and Tent maps (STCS), the other is Logistic-Logistic chaotic system (L-LCS). Based on the two, an image encryption algorithm using dynamic row scrambling and Zigzag transformation is proposed. Firstly, the image is traversed in different directions of odd and even rows, and the results are scrambled with the chaotic sequence generated by STCS. Secondly, based on standard Zigzag scrambling idea, a special traversal method is used, that is, for the different permutation of the lower triangle and the upper triangle of the matrix (each triangular matrix does not contain the values on the main and sub diagonals) in order and direction. Then, combined with the chaotic sequence generated by L-LCS, two different diffusion formulas are used to diffuse the segmented image. Finally, this encryption scheme can also be extended to color images. Experimental simulation and performance analysis show that the encryption algorithm has better security.